Literary Intertextuality of Tomas Venclova‘s Poetry - Nastopka, Kęstutis (Colloquia, 2019)
Borrowing from poetry which belongs to another literary epoch or is written in another language is a constituent part of poetic action. According to Thomas Stearns Eliot, “Immature poets imitate; mature poets steal; bad poets deface what they take, and good poets make it into something better, or at least something different.” In semiotic terms, this can be described as transformation of another poetic language. Algirdas Julius Greimas said: “Meaning is nothing else but transposing one level of language into another level, or one language into another, a different one.” This paper aims to describe the traces of interaction of poets who wrote in different languages and to discuss the direction of transformation of poetic language.The most authoritative teacher of the young Tomas Venclova was Boris Pasternak. The early poems of the Lithuanian poet remind us of Pasternak’s poems from his collection Above the Barriers in their metric variations, rhyming schemes, and alliterative clusters. Two poems by Venclova dedicated to the memory of Pasternak were written in 1960 and 1961. What Venclova ‘steals’ from Osip Mandelstam is mostly semantic figures. In a number of poems, Venclova gets very close to the polyphonic language of this Russian poet. Joseph Brodsky is another constant dialogic partner of Venclova. Sometimes Venclova quotes or paraphrases Lithuanian poetic texts. His poems integrate Lithuanian history of the 20th century, and touch upon the themes of the Holocaust, partisan movement, and the victims of the occupational regime.The values paradigm in Venclova’s poetry is supported by Dante and Shakespeare, as well as a number of 19th and 20th century poets, such as Keats, Baudelaire, Rilke, Apolinnaire or Dylan Thomas. Cyprian Norwid’s “A Funeral Rhapsody in Memory of General Bem” and Czesław Miłosz’s “Ars Poetica?” are also used as poetic subtext. In his later period, Venclova wrote five poems on Biblical stories.Venclova’s connections with the Lithuanian poetic tradition can be defined as hyponymous relationship of belonging: the language and the historical memory. The poetic meanings created by Venclova are actualisations of subtexts of poetry written in many languages. Therefore we can consider Venclova to be a European poet who writes in the Lithuanian language.
Keywords: poetic language; transformation; versification; dialogues; Russian poetry; Western poetry; subtext